Folk speech etiquette: dialogue form - Chekina, Anastasiya (Donetsk State University, 2024)
The article analyzes the peculiarities of the construction of dialogic speech in the form of an etiquette dialogue on the material of field expedition records of the archive "Spiritual Culture of the Russian North in Folk Literature" (SDK) of the Department of Russian Language at St. Petersburg State University. The well-known scientific terms «minimal dialogic unit (MDU)», «dialogicheskoe edinstvo», «dialogovoe edinstvo» are compared, in connection with which the specificity of the etiquette dialogue of folk speech, which is always situationally and thematically conditioned, is revealed. In the analysis, a special attention is paid to the structural and semantic features of the replica-stimulus formula (in the function of greeting, benediction, farewell, etc.), and the replica-reaction formula in their variant variety. The classification of the etiquette dialogue according to the type of response is proposed: "thank you" dialogue, constructor dialogue, chain dialogue. Taking into account the results of the analysis of such constructions, the concept of "etiquette dialogic unity" (EDU) is introduced, which makes it possible to reflect the principal distinguishing features of the dialogic form of etiquette folk speech. The article is carried out in ethnolinguistic aspect.